Afterword: Reflections on Contemporary Educator Movements - Stark, Lauren Ware; Dyke, Erin; Maton, Rhiannon (Critical Education, 2022)
In this afterword, the editors of the special series Contemporary Educator Movements: Transforming Unions, Schools, and Society in North America reflect on the purpose and contributions the series. After reviewing relevant research, they discuss the focus of each of the four issues in the special series as well as themes that appear across the series. Finally, they highlight some of the contributions this series makes to research on social justice unionism and educator organizing.